Acute antioxidant and cytoprotective effects of sulforaphane in brain endothelial cells and astrocytes during inflammation and excitotoxicity - Jianxiong Liu; Giri K. Chandaka; Rong Zhang; Helena Parfenova (Wiley, 2020)
Abstract Sulforaphane (SFN), a bioactive phytochemical isothiocyanate, has a wide spectrum of cytoprotective effects that involve induction of antioxidant genes. Nongenomic antioxidant effects of SFN have not been investigated. Brain oxidative stress during inflammation and excitotoxicity leads to neurovascular injury. We tested the hypothesis that SNF exhibits acute antioxidant effects and prevents neurovascular injury during oxidative stress. In primary cultures of cerebral microvascular endothelial cells (CMVEC) and cortical astrocytes from the newborn pig brain, a pro‐inflammatory cytokine TNF‐α and an excitotoxic glutamate elevate reactive oxygen species (ROS) and cause cell death by apoptosis. Nox4 NADPH oxidase is the main Nox isoform in CMVEC and cortical astrocytes that is acutely activated by TNF‐α and glutamate leading to ROS‐mediated cell death by apoptosis. The Nox4 inhibitor GKT137831 blocked NADPH oxidase activity and overall ROS elevation, and prevented apoptosis of CMVEC and astrocytes exposed to TNF‐α and glutamate, supporting the leading role of Nox4 in the neurovascular injury. Synthetic SFN (10−11‐10−6 mol/L) inhibited NADPH oxidase activity and reduced overall ROS production in CMVEC and astrocytes within 1‐hour exposure to TNF‐α and glutamate. Furthermore, in the presence of SFN, the ability of TNF‐α and glutamate to produce apoptosis in CMVEC and cortical astrocytes was completely prevented. Overall, SFN at low concentrations exhibits antioxidant and antiapoptotic effects in cerebral endothelial cells and cortical astrocytes via a via a nongenomic mechanism that involves inhibition of Nox4 NADPH oxidase activity. SFN may prevent cerebrovascular injury during brain oxidative stress caused by inflammation and glutamate excitotoxicity.